QTL mapping for microtuber ABA content in a diploid potato population - Naz,Raja Mohib Muazzam (2020)
Abstract Abscisic acid (ABA) is known to impact many areas of plant growth and development and is also assumed to facilitate plant stress regulation. ABA is also involved in the rapid suberization of wounds and is the essential dormancy release regulator. The direct application of DNA markers to plant populations enables the use of mapping to help determine the regulation of a quantitatively inherited trait isolated in a population. QTLs represent a chromosomal region that is linked to a marker gene and that significantly affects the quantitative trait under review. In the present study, we investigated the ABA content after harvest and after sprouting in a diploid population. The most noticeable QTLs related to ABA were found on chromosomes I and IV, and these QTLs fully explained 6.5% and 7% of the entire phenotypic variance, respectively. The acquired information advances our understanding of the inheritance of traits applicable for variety development.